Comparison of Knowledge and Attitude Towards Orthodontic Treatment Among High School Students - Dhakal, Jyoti; Shrestha, Manish; Shrestha, Meenu; Acharya, Asal (Orthodontic Journal of Nepal, 2019)
Introduction: Adolescence is the time when a person attains awareness including the self-awareness about his/her health. Hence if proper knowledge is instilled during this time, it will be effective and good oral health behavior can last lifetime. The aim of this study was to assess knowledge and attitude towards orthodontic treatment among the students of public and private schools and compare between them. Materials & Method: A descriptive cross-sectional questionnaire-based study was performed among 700 students (350 from private and 350 from government schools around Kathmandu valley) of grade 8-10. Questionnaire consisted of 14 questions about knowledge and 10 questions about attitude relating to orthodontic treatment. Each response as “yes” was given score ‘1’ and responses “no” and “don’t know” were given score ‘0’. Total score was calculated, followed by mean and compared between that of private and government schools and between genders. Result: No significant difference was found in the knowledge between the students of private and government schools. The difference in attitude score was found to be statistically significant (p=0.00). 54.29% of participants had never heard of an orthodontists, 48.57% never thought that crooked teeth have ill effects, and around 50% of participants were not aware that orthodontic treatment would improve the facial appearance. 47% of participants would not undergo treatment if it took 1-2 years, 53% would not agree for extractions and 42% were not willing to wear retainers. Conclusion: The knowledge and attitude level on orthodontics can be improved by incorporating the basic aspects of oral health in the syllabus of school education.